Simultaneous chemosensing of tryptophan and the bacterial signal molecule indole by boron doped diamond electrode - Buzid, A.; Reen, F.; O'Gara, Fergal; McGlacken, G.; Glennon, J.; Luong, J. (Pergamon, 2018)
A simple and robust chemosensing approach using a boron-doped diamond (BDD) electrode has been developed and applied to analyze tryptophan (TRP) and indole during the growth of Escherichia coli in a complex growth medium. The bacterial enzyme tryptophanase catalyzes TRP to indole, an emerging signaling molecule. The process can now be monitored using electrochemistry, in a method far beyond the traditional identification protocols. Electroanalysis in a non-aqueous medium comprising acetonitrile (ACN) and tetrabutylammonium hexafluorophosphate (TBAH) is capable of separating the oxidation peak of TRP from that of indole. Mechanisms are postulated for the electrochemical oxidation of indole and TRP in ACN chosen because of its wider potential range, proton acceptor property, and solubilization of analytes. The electrochemical oxidation of TRP involves the elimination of two electrons. With a detection limit of 0.5 µM for both indole and TRP, this chemosensing approach is sufficient to monitor the level of these two biomolecules during the bacterial growth period.